2014
DOI: 10.1111/hepr.12316
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing analysis of variants resistant to the non‐structural 5A inhibitor daclatasvir in patients with genotype 1b hepatitis C virus infection

Abstract: Y93H was detected frequently by deep sequencing in daclatasvir treatment-naïve patients. Importantly, it seems that the IL28B status of the patients may influence the presence of Y93H mutations, resulting in different treatment responses to daclatasvir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 28 publications
2
40
3
Order By: Relevance
“…In the present study, both cycling-probe real-time PCR and direct sequencing were performed, and NS5A-Y93H/C mutant HCV strains with a percent RNA level relative to the total HCV-RNA level of 1 % or more were found in 87 patients (19.6 %); these patients were classified into 54 patients (12.2 %) with mixed NS5A-Y93 wild-type and NS5A-Y93H mutant HCV strains and 33 patients (7.4 %) with exclusively NS5A-Y93H/C mutant strains. The percentage of patients with exclusively NS5A-Y93H/C mutant HCV strains was almost equivalent to the value obtained using direct sequencing [21], while the percentage of patients with NS5-Y93H/C mutant HCV strains, including those with mixed NS5A-Y93 wild-type and NS5A-Y93H mutant strains, was relatively close to that obtained using deep sequencing [22]. Thus, our system using cycling-probe real-time PCR combined with direct sequencing seemed to improve the sensitivity of the detection of NS5A-Y93H mutant HCV strains markedly, compared with direct sequencing alone.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the present study, both cycling-probe real-time PCR and direct sequencing were performed, and NS5A-Y93H/C mutant HCV strains with a percent RNA level relative to the total HCV-RNA level of 1 % or more were found in 87 patients (19.6 %); these patients were classified into 54 patients (12.2 %) with mixed NS5A-Y93 wild-type and NS5A-Y93H mutant HCV strains and 33 patients (7.4 %) with exclusively NS5A-Y93H/C mutant strains. The percentage of patients with exclusively NS5A-Y93H/C mutant HCV strains was almost equivalent to the value obtained using direct sequencing [21], while the percentage of patients with NS5-Y93H/C mutant HCV strains, including those with mixed NS5A-Y93 wild-type and NS5A-Y93H mutant strains, was relatively close to that obtained using deep sequencing [22]. Thus, our system using cycling-probe real-time PCR combined with direct sequencing seemed to improve the sensitivity of the detection of NS5A-Y93H mutant HCV strains markedly, compared with direct sequencing alone.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast, Miura et al revealed that such mutant HCV strains were detectable in 30.9 % of Japanese patients with genotype 1b HCV when examined using deep sequencing [22]. In the present study, both cycling-probe real-time PCR and direct sequencing were performed, and NS5A-Y93H/C mutant HCV strains with a percent RNA level relative to the total HCV-RNA level of 1 % or more were found in 87 patients (19.6 %); these patients were classified into 54 patients (12.2 %) with mixed NS5A-Y93 wild-type and NS5A-Y93H mutant HCV strains and 33 patients (7.4 %) with exclusively NS5A-Y93H/C mutant strains.…”
Section: Discussionmentioning
confidence: 92%
“…As such, the antiviral activity can often be overcome by a single mutation. For example, individual SNPs are responsible for resistance of HCV to daclatasvir and of influenza A virus to oseltamivir (14,15). In contrast to the published reports on directly acting antivirals, it is possible that the virus in this study did not undergo enough replication cycles to allow a resistant mutant to develop.…”
Section: Discussionmentioning
confidence: 73%
“…The important role of minor subspecies in accelerated resistance has been shown in various viruses, including HIV (13) and hepatitis C virus (HCV) (12). In the case of HCV and influenza virus, drug-resistant strains arise due to single-nucleotide polymorphisms (SNPs) (14,15), which are easily acquired due to the error rate of the RNA polymerase.…”
mentioning
confidence: 99%
“…The presence of Y93 substitutions in particular confers the highest single-mutation resistance against daclatasvir and other NS5A inhibitors and has been reported to be associated with treatment failure [11,12,[16][17][18]. Although de novo Y93 substitutions may emerge following exposure to daclatasvir, Y93 substitutions in DAA-naïve patients are common in Japan [19,20]. The reason for this high pretreatment frequency is unclear but may reflect differences in the genotype of the host.…”
Section: Introductionmentioning
confidence: 99%